Catastrophic anthropogenic vegetation changes in the Kiliyan arm of the Danube Delta (Ukraine) - Dmytro Dubyna; Tetiana Dziuba; Liubov Borsukevych (Біологічні студії)
Background. Delta areas are unique natural ecosystems, characterized by a high diversity of habitats. At the beginning of the previous century, natural complexes of the Danube Delta underwent significant anthropogenic transformations. Large-scale anthropogenic pressure on natural ecosystems of the delta leads to a catastrophic alteration of the ecological regime and degradation of native flora complexes and plant communities. Catastrophic large-scale changes occurred in the last decades as a result of the damming of the riverbed and near-channel ridges of individual islands, and floodplain territories and their subsequent de-damming, the construction of the large-scale deep-water Danube–Black Sea shipping canal, the transformation of significant areas of delta into agricultural land, pulp backfilling of islands and shallow waters. The coastal ecosystems of the eastern part of the Kiliyan arm of the Danube Delta have also been catastrophically impacted by the Russian military actions, mainly caused by explosions of military shells. Materials and Methods. Long-term comparative phytocoenotic surveys and stationary studies were used in this research. The investigation of the anthropogenic dynamics of vegetation were carried out by direct methods – on stationary and semi-stationary sites. We compared data obtained prior to the construction of the deep-water Danube–Black Sea shipping canal and the recent data obtained after the transformation. The direct methods included the method of comparing the current state with historical maps and geobotanical relevés published in the monograph «Reserve ”Wetlands of the Danube”» (Shelyag-Sosonko & Dubyna, 1984). Results and Discussion. The paper highlights the detected catastrophic anthropogenic vegetation changes based on long-term comparative phytocoenotic surveys and stationary studies. Catastrophic changes in the vegetation of the Danube Delta most pronounced on the territory of Stentsivsko-Zhebryansky floodplain, the Zhebryansk seaside ridge, Yermakov, Mashenka, Katenka, Kislytsky, Maly and Velyky Tataru, Velyky and Maly Dallery islands, in the area of Izmail and Ust-Dunaisk ports, the floodplain zone near the city of Kilya, and most of the floodplain terrace from Vylkovo to Izmail. The most endangered are meadow and psammophyte vegetation with representatives of the psammophilous-littoral neoendemic floristic complex. The floodplain forests are also subject to digression. Only aquatic ecosystems are more labile to hydrological changes. Conclusion. A strategy for optimizing the vegetation cover of the delta is offered. The established patterns can be used to develop methods for assessing the risks for ecosystems, and the intensity of their degradation to ensure effective protection, management, and sustainable use of the biodiversity in the delta areas of the Northern Black Sea region.